The Effect of Classical Music on Dysmenorrhea Pain in Medistra Lubuk Pakam Midwifery Students - Sri Wulan; Siti Mutiara Zam Zam; Kesya Dia Ramadani; Shalwa Fatona (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Dysmenorrhea, or menstrual pain, is a common problem frequently experienced by women of reproductive age, including university students. This condition can negatively affect quality of life, disrupt daily routines, and even lower academic performance. For midwifery students, who often have demanding academic and clinical practice schedules, unmanaged menstrual pain can impact study focus, clinical performance, and overall psychological well-being. Therefore, it is important to understand the severity of pain as a basis for selecting appropriate management strategies. One non-pharmacological treatment method used is classical music therapy, as its calming effect is believed to help reduce pain intensity. This study aims to evaluate the effect of classical music therapy on reducing dysmenorrhea pain levels among Midwifery students at Medistra Lubuk Pakam. The research design used was a quasi-experimental approach with a pretest-posttest design without a control group. The study participants consisted of 30 students experiencing dysmenorrhea, selected through purposive sampling. The intervention involved playing classical music for 30 minutes per day over three consecutive days during menstruation. Pain levels were measured using the Visual Analog Scale (VAS) before and after the intervention. The results showed a significant decrease in pain after classical music therapy was administered (p < 0.05), indicating that classical music is effective in alleviating menstrual pain. Based on these findings, classical music can be considered a viable non-pharmacological therapy option for reducing dysmenorrhea among midwifery students. This study is expected to serve as a reference for more comprehensive approaches to managing dysmenorrhea.